2019
DOI: 10.1093/mnras/stz1484
|View full text |Cite
|
Sign up to set email alerts
|

On the Oosterhoff dichotomy in the Galactic bulge – II. Kinematical distribution

Abstract: We present a kinematical study of RR Lyrae stars associated with two Oosterhoff groups in the Galactic bulge. We used data published in the first paper of the series, plus proper motions from the Gaia Data Release 2, and radial velocities from the literature. A 6D kinematical and spatial solution was obtained for 429 RR Lyrae stars. We use a model of the Galactic gravitational potential to infer stellar orbits. We did not find a difference between the Oosterhoff groups in the individual components of the space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…6 (dark point, v θ = 415 kms −1 and v R = −224 kms −1 ), AO Peg, with [Fe/H]= −0.92 dex and a space velocity sv = 512 km s −1 . In general, for only 2 % of the RR Lyrae pulsators from our sample the sv exceed 400 km s −1 , which is similar to RR Lyrae stars in the Galactic bulge sample (Prudil et al 2019c) where we found roughly 3 % of the RR Lyrae stars to show sv above 400 km s −1 .…”
Section: Velocity Componentssupporting
confidence: 60%
See 1 more Smart Citation
“…6 (dark point, v θ = 415 kms −1 and v R = −224 kms −1 ), AO Peg, with [Fe/H]= −0.92 dex and a space velocity sv = 512 km s −1 . In general, for only 2 % of the RR Lyrae pulsators from our sample the sv exceed 400 km s −1 , which is similar to RR Lyrae stars in the Galactic bulge sample (Prudil et al 2019c) where we found roughly 3 % of the RR Lyrae stars to show sv above 400 km s −1 .…”
Section: Velocity Componentssupporting
confidence: 60%
“…In general, these variables are not used as probes of the Galactic disc, although they have been used successfully to put constraints on the structure of the thick disc and the mechanisms that contributed to its formation (Kinemuchi et al 2006;Kinman et al 2009;Mateu et al 2012;Mateu & Vivas 2018;Dékány et al 2018). Kinematic studies using RR Lyrae stars in the solar neighbourhood (e.g., Layden et al 1996;Maintz & de Boer 2005;Marsakov et al 2018) and in the Galactic bulge (Kunder et al 2016(Kunder et al , 2019Prudil et al 2019c), suggest that a small fraction of nearby RR Lyrae variables might be associated with the Galactic disc and the old spheroidal component of the Galactic bulge whereas most of them belong to the halo. Mainly the work by Layden et al (1996) and Marsakov et al (2018Marsakov et al ( , 2019a link some of the local RR Lyrae stars to the Galactic disc based on their kinematical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis shows that about 25% of bulge RR Lyrae belong to the halo population (see Figure 4 of Pietrukowicz et al 2020b), which is in excellent agreement with spectroscopy-based results by Kunder et al (2020) based on the BRAVA-RR data, who found that 25% of bulge RR Lyrae are halo interlopers (see their Figure 6), but is slightly more than the 9% reported by Prudil et al (2019) based on a kinematical study of bulge RR Lyrae. Kunder et al (2020) also showed that, once the halo interlopers are removed from the bulge sample, we can clearly see two populations of RR Lyrae that are spatially and kinematically different.…”
Section: The Bulge In Rr Lyraesupporting
confidence: 83%
“…RR Lyrae stars with high velocities have been identified in the Galactic bulge by the Bulge Radial Velocity Assay for RR Lyrae stars (BRAVA-RR, Kunder et al 2015;Prudil et al 2019;Kunder et al 2020) and one of them was subsequently followed up by a spectroscopic study (Hansen et al 2016). All of these appear to be bound and kinematically associated with the MW halo (although currently passing through the Galactic bulge), nonetheless, they provide important insight into the high-velocity distribution of the old population in the Galactic center.…”
Section: Introductionmentioning
confidence: 99%